2013
DOI: 10.1002/adma.201302495
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mechanical Properties of Graphene/Copper Nanocomposites Using a Molecular‐Level Mixing Process

Abstract: RGO flakes are homogeneously dispersed in a Cu matrix through a molecular-level mixing process. This novel fabrication process prevents the agglomeration of the RGO and enhances adhesion between the RGO and the Cu. The yield strength of the 2.5 vol% RGO/Cu nanocomposite is 1.8 times higher than that of pure Cu. The strengthening mechanism of the RGO is investigated by a double cantilever beam test using the graphene/Cu model structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
301
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 636 publications
(316 citation statements)
references
References 32 publications
8
301
2
5
Order By: Relevance
“…Many previous studies have focused on designing and fabricating new graphene reinforced metal matrix composites, including aluminum [7][8][9], copper [10,11], magnesium [12], and nickel matrix composites [13,14]. In most cases, it was observed that the mechanical properties were significantly enhanced, even with the addition of a very small amount of graphene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have focused on designing and fabricating new graphene reinforced metal matrix composites, including aluminum [7][8][9], copper [10,11], magnesium [12], and nickel matrix composites [13,14]. In most cases, it was observed that the mechanical properties were significantly enhanced, even with the addition of a very small amount of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile strength of a 0.3 wt % graphene nanosheet (GNS)-reinforced Al composite increased by 62% compared with that of the unreinforced matrix [9]. The elastic modulus and yield strength of graphene/copper nanocomposites containing 2.5 vol % reduced graphene oxide were 131 GPa and 284 MPa, which were 1.3 and 1.8 times higher, respectively, compared with those of pure Cu [11]. Kim et al synthesized a metal-graphene nanolayered composite and found that the addition of GNS resulted in an ultra-high strength of 4.0 GPa for a graphene/nickel composite [14].…”
Section: Introductionmentioning
confidence: 99%
“…Because the graphene was uniformly dispersed in the solution, it would be the nucleating agent and Cu OH 2 would be adsorbed onto the monolayer grapheme [7], thereby CuO/graphene composites were formed. After standing, the precipitate was filtered, washed and dried to obtain a dried CuO/graphene composite.…”
Section: Gcmm Matecconf/201 4010mentioning
confidence: 99%
“…In biomedical field, graphene have been utilized as scaffolding in tissue engineering, as an internal component of power unit for biomedical devices, in drug delivery and cancer therapy and in biosensors, due to its ultra-high sensitivity, unique morphological characteristics and strong mechanical properties. The unique monoatomic structure of graphene offers remarkable physical properties such as high mechanical strength with 1 TPa Young's Modulus and 130 G Pa tensile strength for single graphene layer (Hwang et al 2013), high transparency of 97.7% for single layer, high conductivity and high carrier mobilities up to 10 5 cm 2 V -1 s -1 , which is 2-3 orders of magnitude higher than the conventional semiconductor such as silicon (Hwang et al 2013). These excellent physical properties are advantageous in biomedical applications, particularly in tissue engineering, where graphene is utilized as a scaffolds for tissue growth (Goenka et al 2014).…”
Section: Introductionmentioning
confidence: 99%